The Relationship Between Leadership Quality and Work Climate With Work Motivation Employees In The Administrative Department Of Junior High Schools In Gorontalo City - Ansar, Ansar; Tune Sumar, Warni; Laiya, Nurain (Devotion : Journal of Research and Community Service, 2023)
This study aims to determine: 1) The Relationship between Leadership Quality and Employee Work Motivation at SMP Se Kota Gorontalo. 2) The Relationship between Work Climate and Employee Work Motivation at SMP Se Kota Gorontalo. 3) Leadership Quality Relationships and Work Climate together with Employee Work Motivation at SMP Se Kota Gorontalo. The method used is quantitative, with correlational techniques. The technique of collecting data using questionnaires. The results of this study show that Leadership Quality with Employee Work Motivation has a significant relationship with a correlation coefficient of 0.171 or 17.1 %, 2) Work Climate with Motivation Employee Work has a significant relationship with a correlation of coefficients of 0.221 or 22.1 %, 3) Leadership Quality and Work Climate with Work Motivation Employees have a relationship that significant with a correlation coefficient of 0.542 or 54.2%. For this reason, it is recommended: 1) For institutions, this research is expected to be useful as information material to add knowledge and insight so that even in this research can improve performance employees. 2) For employees, this research is expected to be able to understand , understand and have a sense of responsibility to the work and become a benchmark in quality and The working climate for the results of work is in accordance with the expectations of the institution